Ozônio penetrante como agente de eliminação de pragas em peças estruturadas - Gonçalves, Gustavo (Universidade Federal de São Carlos, 2026)
The application of ozone in decontamination processes is highly relevant due to its oxidizing, disinfecting, and sanitizing capacity. Its versatility enables the reduction of chemical and microbiological contaminants in different matrices, including agricultural products, water, effluents, surfaces, and porous materials. In addition, ozone represents a sustainable alternative to conventional agents because it rapidly decomposes into molecular oxygen and, when complete mineralization of contaminants occurs, does not generate residues harmful to the environment. However, its effectiveness in solid structures may be limited by its low penetration capacity into cavities, pores, and internal galleries. In this study, a portable system intended for termite control in furniture, works of art, and objects of historical value was developed and evaluated, based on the sequential application of vacuum and ozone under a controlled atmosphere. The vacuum stage was employed to partially remove the air trapped within the materials and to promote the diffusion of the oxidizing gas into hard-to-reach regions. Experimental validation was performed using individuals of the species Coptotermes gestroi, subjected to different combinations of ozone concentration, vacuum pressure, relative humidity, exposure time, and number of cycles. In tests conducted in 500 mL vessels, the combination of 65,000 ppm ozone and 500 mmHg vacuum resulted in 95.6% mortality, whereas the same ozone concentration without vacuum application produced a lower mortality rate. In tests carried out in 8 L vessels, 100% mortality was achieved after three cycles at a relative humidity of 50 ± 5%, while under a condition of 70 ± 5% relative humidity, mortality was approximately 85%, demonstrating the influence of humidity on ozone stability and biocidal efficiency. In the enlarged-scale validation, using a 40 L vessel containing organic matter with microcavities, cumulative mortality reached 96.11% after three treatment cycles. The results emonstrated that the association between vacuum and ozone enhances biocidal action, increases gas availability within cavities and internal regions of the substrates, and improves process efficiency across different application scales. No perceptible physical changes were observed in the evaluated materials after the treatment cycles. The developed system demonstrated effectiveness, portability, reproducibility, and potential application in termite eradication and the decontamination of sensitive materials, constituting a sustainable alternative to conventional chemical methods and contributing to the development of technologies aimed at heritage conservation and integrated pest management.
Penetrating ozone as an agent for pest elimination in structured components
Keywords: Ozônio; Descontaminação; Sanitização; Cupins; Museus; Ozone; Pest control; Decontamination; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::ECOLOGIA APLICADA A ENGENHARIA SANITARIA; 9. Indústria, Inovação e Infraestrutura